ANALISIS KONTRIBUSI SEKTOR INDUSTRI PENGOLAHAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KABUPATEN BOJONEGORO - Endang (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2018)
This study aims to determine the size of the contribution of the manufacturing sector to Gross Regional Domestic Product Bojonegoro and estimate how much increase of Gross Regional Domestic Product of Bojonegoro Regency in manufacturing industry sector in 2017 and 2018. The type of data used in this study is secondary data. Method of data analysis in this study to calculate the growth rate of manufacturing industry sector and to calculate the contribution of industrial sector of processing used analysis of Sjafrizal, 2016. To make forecasts used analysis from J. Supranto, 2010. The result of analysis is the value of production of processing industry sector from year to year has increased but the contribution of manufacturing industry sector to GRDP is increasing and decreasing. In 2011, the contribution of manufacturing industry sector to GRDP of Bojonegoro Regency was 5.79% and in 2012 it was 5.88%, in 2013 of 6.02% increase, and in 2014 increased by 6.26%, year 2015 amounted to 5.61% decreased, and in 2016 amounted to 4.83% decline. Forecast the growth of Bojonegoro Industrial Processing Industry sector in 2017 amounted to 3.39% decreased and growth in 2018 increased by 5%.